2011
DOI: 10.1002/agr.20274
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the implications of regional preferential market access for meat commodities

Abstract: The authors derive a gravity framework that is compatible with the existence of reference prices for agricultural commodities. A commodity-specific gravity equation, estimated with Poisson pseudomaximum likelihood and threshold Tobit estimators, is used to investigate the effects of regional trade preferences for meat commodities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Endnote a Many empirical studies (e.g., Sarker and Jayasinghe, 2007;Grant and Lambert, 2008;Lambert and McKoy, 2009;Sun and Reed, 2010;Ghazalian et al, 2011) reported increasing effects of several RTAs on international trade in agricultural products between member countries (i.e., trade creation effects), which often significantly exceed the decreasing effects of these RTAs on international trade in agricultural products between member countries and non-member countries (i.e., trade diversion effects). b Funk (2003) found that increases in import competition levels have reduced Research and Development (R&D) activities of manufacturing firms in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Endnote a Many empirical studies (e.g., Sarker and Jayasinghe, 2007;Grant and Lambert, 2008;Lambert and McKoy, 2009;Sun and Reed, 2010;Ghazalian et al, 2011) reported increasing effects of several RTAs on international trade in agricultural products between member countries (i.e., trade creation effects), which often significantly exceed the decreasing effects of these RTAs on international trade in agricultural products between member countries and non-member countries (i.e., trade diversion effects). b Funk (2003) found that increases in import competition levels have reduced Research and Development (R&D) activities of manufacturing firms in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…According to Leamer and Levinsohn (), the negative effect of the geographic distance on international trade flows is one of the clearest and most robust empirical findings in international economics. The empirical gravity literature on international trade in primary agricultural and processed food products generally focuses on investigating the implications of trade policy barriers (e.g., tariffs, nontariff barriers) and Preferential Trade Agreements (PTAs) for international trade (Ghazalian, Larue, & Gervais, ; Ghazalian, Tamini, Larue, & Gervais, ; Grant & Lambert, ; Haq, Meilke, & Cranfield, ; Koo, Kennedy, & Skripnitchenko, ; Lambert & McKoy, ; Olper & Raimondi, ; Sarker & Jayasinghe, ; Susanto, Rosson, & Adcock, ; Sun & Reed, ). This literature also reports substantial overall negative distance effects on primary agricultural and processed food trade.…”
Section: Introductionmentioning
confidence: 99%
“…In the EU market, developing countries have been responsible for 60% of the total import value of seafood products during the last decade (Table 1). At the same time, the seafood trade contributes substantially to the economies of developing countries in terms of foreign exchange earnings and labor employed (Panagariya 2002;Bostock, Greenhalgh, and Kleih 2004; Béné, Lawton, and Allison 2010;Ghazalian, Larue, and Gervais 2011). The duty-free access under the GSP-plus arrangement would be extended to include more seafood products from developing countries, which are currently outside the standard EU'S GSP arrangement.…”
Section: Introductionmentioning
confidence: 99%